Cell pretreatment with ethylenediaminetetraacetic acid for selective extraction of C‐phycocyanin with food grade purity. (3rd October 2018) - Sala, Luisa; Moraes, Caroline Costa; Kalil, Susana Juliano
Abstract : C‐phycocyanin (C‐PC) is a natural blue dye, and depending on its purity, which is measured by the ratio between the absorbance of the chromophore (A620 ) and the absorbance of the proteins (A280 ), it can be used in food (purity > 0.7), cosmetics (purity > 1.5), and therapeutic treatments (purity > 4.0). Several physical, chemical, and enzymatic methods of extraction are reported, however, few are able to extract C‐PC with purity above 0.7. An innovative method of C‐PC extraction with food grade purity from wet Spirulina platensis biomass is proposed. The cells were pretreated with ethylenediaminetetraacetic acid and subsequent C‐PC extraction was performed with tris‐(hydroxymethyl) aminomethane‐SO4 buffer. C‐PC was released after 12 h of cell pretreatment. Six variables of the extraction process were evaluated. The extraction temperature significantly influenced C‐PC extraction yield and purity. In the best condition of cell pretreatment and extraction, C‐PC with purity of 1.0 and extraction yield of 129.0 mg/g could be obtained to be used as a food dye without any purification process. Lastly, an ultrafiltration process was integrated and C‐PC was concentrated 8.8‐fold, resulting in purity of 1.6 and recovery of 93.4%.